Sensor insole for measuring temporal variables and vertical force during sprinting - Nagahara, R.; Morin, J.-B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Temporal variables and vertical ground reaction force have been used as measures characterizing sprinting. A recently developed wireless pressure sensor insole (sensor insole) could be useful for monitoring sprinting in terms of temporal variables and vertical ground reaction force during training sessions. The purpose of this study was to examine the concurrent validity of the sensor insole for measuring temporal and vertical force variables during sprinting. One athlete performed five 50-m sprints, and the step-to-step vertical ground reaction force and plantar pressure were simultaneously measured by a long-force platform system (reference device) and the sensor insole, respectively. The temporal and vertical ground reaction force variables were calculated using signals from both devices, and a comparison was made between values obtained with both devices for 125 steps analyzed. The percentage bias, 95% limits of agreement, and Bland-Altman plots showed low agreement with the reference device for all variables except for step frequency. For the vertical ground reaction force variables, the sensor insole underestimated the values (-18.9 to -48.3%) compared to the force platform. While support time and time to maximal vertical force from the foot strike were overestimated by the sensor insole (54.6 ± 8.0% and 94.2 ± 23.2%), flight time was underestimated (-48.2 ± 15.0%). Moreover, t-test revealed the significant difference in all variables between the sensor insole and force platform, except for step frequency. The bias for step frequency (0.4 ± 7.5%) was small. However, there was heteroscedasticity for all variables. The results from this study demonstrate that a wireless pressure sensor insole is generally not valid to measure the temporal and vertical force variables during sprinting. Thus, using the examined sensor insole for monitoring sprinting characteristics is not recommended at this time.